Some observations on the breakage of ultrasonic files driven piezoelectrically - Ahmad, M; Roy, R (Wiley, 1994)
The incidence of breakage of Piezon‐Master ultrasonic K files were evaluated. Three groups of unused files were subjected to three treatments, namely; free vibration in air without irrigation, free vibration in root canal while minimizing contact with the wall of canal in the presence of irrigation and light filing in root canal with free flow of irrigation. Cavitation produced by files in contact and free of contact with a glass surface was examined in order to observe the relationship between cavitation defects and breakage. In addition, the fractured and un‐fractured files were examined under a scanning electron microscope for the presence of cavitation pits. The results indicated that more files broke in air. In water, a higher incidence of breakage occurred when files were allowed to freely vibrate while no breakage occurred when the files were used in filing. All files generated cavitation which resulted in pitting of their surfaces. However, it was considered unlikely that the pits contributed to fracture. Fatigue cracks which could be the result of the manufacturing process were observed at some of the corners of the cross sections of the fractured files and could be the main contributory‐factor to fracture.